1997
DOI: 10.3109/08037059709062084
|View full text |Cite
|
Sign up to set email alerts
|

Heart Function in Patients with Chronic Glomerulonephritis and Mildly to Moderately Impaired Renal Function: An Echocardiographic Study

Abstract: in a group of patients with chronic glomerulonephritis and mildly to moderately impaired renal function, it was found by means of echocardiography that there was a higher LV mass index and decreased systolic function, when compared with healthy controls. In addition, the patients had diastolic dysfunction of primarily the left ventricle. The echocardiographic findings were not correlated to BP level or renal function. This suggests that factors other than GFR or BP per se might be involved in the pathogenesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 43 publications
3
18
0
Order By: Relevance
“…33 and the presence of commonly associated comorbidities such as hypertension, diabetes, and anemia explain only part of the left ventricular remodeling. [44][45][46] The molecular basis for these changes includes activation of growth factors, proto-oncogenes, plasma noradrenalin, cytokines, and angiotensin II. These factors regulate intracellular processes that accelerate cardiac hypertrophy, myocardial fibrosis, and apoptosis.…”
Section: Possible Mechanismsmentioning
confidence: 99%
“…33 and the presence of commonly associated comorbidities such as hypertension, diabetes, and anemia explain only part of the left ventricular remodeling. [44][45][46] The molecular basis for these changes includes activation of growth factors, proto-oncogenes, plasma noradrenalin, cytokines, and angiotensin II. These factors regulate intracellular processes that accelerate cardiac hypertrophy, myocardial fibrosis, and apoptosis.…”
Section: Possible Mechanismsmentioning
confidence: 99%
“…LV mass has also been related to proteinuria and microalbuminuria in such patients (5,21,22). As for LV function, it has been reported that patients with renal insufficiency had both systolic and diastolic dysfunction (23). Furthermore, weak associations have been shown between microalbuminuria and indices of LV diastolic function (5).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, among participants with CKD most advanced dialysis, magnetic resonance imaging (MRI) contrast exhibits a diffuse pattern image with gadolinium uptake, suggestive of fibrosis and nonischemic cardiomyopathy [37]. The pathogenesis of these conditions is considered manifold [38][39][40]. CKD is also associated with vascular disease, including calcification and inurement of the blood vessels [41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%